Methodological strategies to improve communication skills in English language - Rosales Moreira, Diana Lisbeth (2023)
Through this case study, several important outlooks could be exanimated, which have a great impact when organizing an English as a foreign language class. Each one of them was analyzed based on a real scenario where some characteristics were found to be taken into account when planning the lesson to be taught, in order to counteract the possible drawbacks that may arise. In this case study are some of the difficulties surrounding teaching-learning. From the peculiarities of teaching young learners between 15 and 16 years old, and the disadvantages of being in an overcrowded classroom, which hinder the existence of a real and meaningful learning with greater reach for all students in teaching young learners. As a result, the cooperative learning strategy will be used to promote communication skills in the classroom, at the “Unidad Educativa Fiscomisional Americano”, since it has certain student collaboration techniques which can be adapted to the specific needs of Learners. The techniques of group work, self-assessment and peer-assessment will be used mostly in the planning to maximize the scope of the teaching, with the help of the benefits of the exchange of opinions, ideas and knowledge among peers.